Age difference in the combined effect of soda drinks consumption and body adiposity on hyperuricaemia in US adults. Issue 17 (5th December 2021) - Lin, Wei-Ting; Kao, Yu-Hsiang; Lin, Hui-Yi; Li, Mirandy S; Luo, Ting; Fritz, Jackson M; Seal, David W; Lee, Chien-Hung; Hu, Chih-Yang; Tseng, Tung-Sung
Abstract: Objective: To evaluate age-related differences in the independent/combined association of added sugar intake from soda and body adiposity with hyperuricaemia in gender-stratified US adults. Design: Consumption of added sugar from soda was calculated from 24-h dietary interviews and categorised into none, regular and excessive consumption. Hyperuricaemia was defined as serum uric acid levels >417 mmol/l in men and >357 mmol/l in women. Multiple regression models with interaction terms and logistic models adjusted for covariates were conducted under survey-data modules. Setting: National Health and Nutrition Examination Survey during 2007–2016. Participants: 15 338 adults without gout, failing kidneys, an estimated glomerular filtration rate < 30 or diabetes were selected. Results: The age-stratified prevalence rate of hyperuricaemia was 18·8–20·4 % in males and 6·8–17·3 % in females. Hyperuricaemia prevalence of approximately 50 % was observed in young and middle age males who consumed excessive added sugar from soda. Excessive added sugar intake was observed to be associated with 1·5- to 2·0-fold and 2·0- to 2·3-fold increased risk of the probability of hyperuricaemia in young and middle age males and middle age females, respectively. Study participants, regardless of age or gender, who were obese and consumed excessive added sugar from soda had the highest risk of having hyperuricaemia. Conclusions: Our study revealed that the association between hyperuricaemia and consumption of excessive added sugar from soda may vary by age and gender. Obese adults who consumed excessive added sugar from soda had the highest risk of hyperuricaemia, a finding that was found across all age-specific groups for both genders.